trig
posted by Piwokazi .
Help find the general solution to:sin^2x3cosx+sinxcosx3sinx=0

trig 
Reiny
sin^2x3cosx+sinxcosx3sinx=0
sin^2x  3sinx + sinxcosx  3cosx = 0
sinx(sinx  3) + cosx(sinx  3) = 0
(sinx  3)(sinx + cosx) = 0
sinx = 3 , which is not possible
or
sinx = cosx
sinx/cosx = 1
tanx = 1
x = 135° or 225° or in radians, 3π/4 , 5π/4
the period of tanx = 180° or π radians
general solution: = 3π/4 + kπ
or
x = 5π/4 + kπ , where k is an integer
Respond to this Question
Similar Questions

trig
find the exact solutions 2cos^2x+3sinx=0 the way it stands, that is a "nasty" question. Are you sure the second term isn't 2sin(2x) ? 
Trigonometry.
( tanx/1cotx )+ (cotx/1tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side … 
trig
What is the shift along x of the following trig functions? 
Math
1. Find y'(x) when xsecy  3y sinx = 1 a) (3ycosx  sec y) / (xsec^2y  3sinx) b) (3cosx  sec x) / (xsecytany  3sinx) c) (3ycosx  sec y) / (xsecytany  3sinx) d) (3ycosx  secytany) / xsec^2y  3sinx) This is what I did: xsecy  … 
TRIG!
Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1  (3/4)sin^2 2x work on one side only! Responses Trig please help!  Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 … 
trig
What's the general solution for 3sin^2x+sinxcosx=2 
trig
Help find the general solution to:sin^2x3cosx+sinxcosx3sinx=0 
trig identites
since sin2x+√3cos2x=2sin(2x+60) find the general solution for the equation sin2x+√3cosx=0 thank you 
Precalculus/Trig
Prove the following identity: 1/tanx + tanx = 1/sinxcosx I can't seem to prove it. This is my work, I must've made a mistake somewhere: Converted 1/tanx: 1/sinx/cosx + sinx/cosx = 1/sinxcosx Simplified 1/sinx/cosx: cosx/sinx + sinx/cosx … 
Precalculus/Trig
I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1  cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1cosx Simplified: cosx + sin^3x/sin^3x = cscx/1cosx I don't know …